Nisbah Antara Ilmu Pengetahuan, Filsafat, dan Agama - Yasmin, Nur Asyiffa Amalia; Nursandi, Nuri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Science functions to search for scientific truth. In the Islamic view, knowledge is considered important for humans to achieve worldly prosperity and deepen their knowledge of God. This article aims to examine the definition of science, its characteristics, as well as the similarities and differences between science, religion and philosophy. Science, religion and philosophy are three elements that can guide humans in their search for truth, but they have significant differences. This article uses the Library research discussion method. This method relies on scientific works that have been published by researchers as the main data source. In this context, research is called